School Dropout and Adaptive Resilience: Understanding Adolescents’ Educational Choices in Muslim Marginalized Communities - Ahmad Fadlolul Abror; Aman Sahin Bin Mehra; Choirunnajih Hadanil Alqo; Muhamad Rayhan Al Arif; Nurus Syifa'ur Rohmah; Aang Kunaepi (Journal of Islamic Education Thought and Development, 2026)
This study aims to uncover the meaning behind the phenomenon of school dropout among adolescents in Islamic marginalized communities, Lamongan City, Indonesia. This phenomenon is often negatively stigmatized as academic failure alone without understanding the underlying context. Using a qualitative approach with an in-depth case study design, data were collected through unstructured interviews, participant observation, and analysis of village archive documents, then systematically analyzed using the Miles and Huberman interactive model. Data validity was ensured through rigorous source triangulation. The results indicate that school dropout in this region is a manifestation of the tension between immediate economic needs and the long-term value of education. Economic factors and the tradition of early marriage force adolescents to adopt a pragmatic view that prioritizes immediate family financial contributions over continuing formal schooling. However, crucial findings reveal the presence of regret and hope in breaking the cycle of poverty, indicating that motivation to learn is not lost but rather shifted to mastering vocational skills as a means of survival. This dynamic confirms that the decision to drop out of school is not a rejection of education itself, but rather a rational adaptation strategy to environmental conditions that require facilitative policy interventions in the form of alternative educational pathways. This research contributes to the development of Islamic education by emphasizing the need for inclusive, community-based, and value-oriented educational models that integrate social resilience, vocational empowerment, and humanistic Islamic principles in addressing school dropout among marginalized adolescents